Faktor-faktor yang memengaruhi loyalitas pelanggan (Studi pada Generasi Z pengguna e-commerce) - Yuantomo, Benedictus Okta; Keni, Keni (Jurnal Manajemen Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the influence of perceived ease of use and flash sale on customer loyalty, with customer satisfaction as a mediating variable among Generation Z users of an e-commerce platform. The background of this research is the high level of e-commerce competition, which necessitates the importance of customer loyalty for business sustainability. The research method uses a quantitative approach with a non-probability sampling technique, specifically purposive sampling, involving a total sample of 242 valid Generation Z respondents in the Java and Bali regions. Data was collected through online questionnaires, and the data analysis technique used was Partial Least Square – Structured Equation Modelling (PLS-SEM). The research findings indicate that perceived ease of use and flash sale have a positive and significant effect on customer satisfaction and customer loyalty. Customer satisfaction was also proven to have a positive and significant effect on customer loyalty. Furthermore, the findings show that customer satisfaction significantly mediates (partial mediation) the influence of perceived ease of use and flash sale on customer loyalty. In conclusion, enhancing application ease of use and relevant flash sale strategies can effectively increase satisfaction, which in turn contributes significantly to building and improving the customer loyalty of Generation Z. Theoretically, this study confirms the mediating role of satisfaction in linking technical features and sales promotion to Gen Z loyalty. Practically, management needs to prioritize interface innovation for seamless transactions and design relevant flash sale programs to maintain customer loyalty.